Prevalence of methicillin-resistant Staphylococcus aureus in residents who died with pressure ulcers in residential aged care facilities - Sharp, Catherine (Asian Journal of Medical Sciences, 2024)
Background: As mobility in the elderly declines, dependence on care increases, and that care involves preventing pressure ulcers (PUs). PUs may become colonized with methicillin-resistant Staphylococcus aureus, causing cross-infection problems and leading to sepsis and death. Aims and Objectives: The aim of this paper was to examine the prevalence of methicillin-resistant S. aureus in residents with PUs and consider regulations. Materials and Methods: A retrospective review of 80 records of residents aged ≥65 years from eight residential aged care facilities (RACFs) in Australia was undertaken. Records were reviewed for sex, age at death, source of admission, Stage of PU, and colonization with methicillin-resistant S. aureus. Results: A third of residents, 34% (95% confidence interval [CI] 25%–44%, 27/80), had PUs in the last week of life. Of residents admitted from hospital 13% (95% CI 9%–32%, 7/40) had PUs. Most (63%, 95% CI 44–78%, 17/27) residents with a PU had been admitted from hospital, and most PUs (78%, 95% CI 59–89%, 21/27) were open wounds, stages 2–4. Half of all residents with a PU (48%, 95% CI 30–67%, 13/27) were colonized with methicillin-resistant S. aureus, and a third of residents with stages 2–4 PUs (31%, 95% CI 13–58%, 4/13) were colonized with methicillin-resistant S. aureus. Conclusion: Nearly half of all PUs were colonized with methicillin-resistant S. aureus, suggesting PUs may be a reservoir for methicillin-resistant S. aureus. Regulations that could reduce PUs in RACFs “an air mattress appropriate to each care recipient’s condition” are not being utilized. If PUs were prevented, reservoirs for methicillin-resistant S. aureus would be eradicated.